China Goes Global. - Chang, Julian (International Journal of Emerging Markets: Volume 9, Issue 2., 2014)
Constituting over two-thirds of the world's population and one-fifth of its GDP, the emerging markets are expected to continue to impact the world's new economic order, ushering in changes in economic thought, management philosophy, global operations, and financial flows. Given their importance to the global economy, the emerging markets are an important testing ground for existing models and concepts in international business, management, marketing, economics, and finance, pushing the boundaries of existing theories. They are also fertile ground for developing new models and theories with dif.